Haemosporidian infection is related to the expression of female plumage ornamentation in a wild passerine - González-Bernardo, Enrique; Moreno-Rueda, Gregorio; Camacho, Carlos; Muriel, Jaime; Martínez-Padilla, Jesús; Potti, Jaime; Canal, David (Elsevier, 2025)
The role of plumage ornamentation as a signal of parasite infection is a key issue in the evolution of animal behaviour. Despite the undeniable role of host–parasite interactions in sexual selection, it is still unclear how parasites influence the variance in the expression of females displaying multiple ornaments. Here, by taking advantage of a long-term and individual-based, monitored population of pied flycatchers, Ficedula hypoleuca, in a Mediterranean area, we investigated the variation in the expression of wing patch (size) and forehead patch (occurrence and size) in relation to infections with haemosporidian parasites in breeding adult females. Haemosporidian infection was related to wing patch size, and this association varied in direction and magnitude depending on the origin of birds (locally born versus immigrant) and the type of breeding habitat (oakwood versus pine plantation). Specifically, differences in wing patch size were most evident among immigrant females breeding in the pine plantation, with noninfected females expressing larger wing patches than infected ones. Regarding the forehead patch, its occurrence was also modulated by haemosporidian infection through two-way interactions with bird origin (lower occurrence in locally born females) and breeding habitat type (lower occurrence among infected than uninfected females in the oakwood, whereas the opposite was true in the pine plantation). Only bird age predicted forehead patch size. Therefore, in addition to haemosporidian infection, the expression of these ornaments was related to extrinsic (breeding habitat) and intrinsic (age, origin) factors, which suggests the existence of trade-offs between physiological responses to infection and the expression of secondary sexual traits. Overall, our results suggest that plumage ornaments provide independent and reliable information on the haemosporidian infection status of female pied flycatchers.